Approach to scientific portal development - Globa, Larysa; Novogrudska, Rina (Видавництво Львівської політехніки, 2012)
in this paper the approach to designing the functional knowledge internet-portal is shown, as well as problems of qualitative knowledge representation on portal are solved and integration of computational tasks and informational recourses of portal are given.
Keywords: portal; knowledge representation; computational tasks; ontology; model